2019
DOI: 10.1177/0192513x19886647
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Parenting Style, Alexithymia and Aggression in Emerging Adults

Abstract: Alexithymia has been linked to reduced emotional awareness and increased aggression. One line of evidence suggests that authoritarian parenting contributes to the development of alexithymia. To elucidate the relationship between experienced parenting style, alexithymia and aggression the Parental Authority Questionnaire, the Toronto Alexithymia Scale and the Buss–Perry Aggression Questionnaire were administered to a group of emerging adults. Current findings show a positive relationship between: (i) authoritar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 81 publications
4
7
0
1
Order By: Relevance
“…Children do not only inherent physical features but also acquire and learn identity, values, interpersonal skills, self-esteem, and self-concept (Rohner, 2004;Shim & Lim, 2019). Affectionate, warmth, positive, caring, and supportive relationship with parents aids the children to develop aninternal model (Bowlby, 1982) which assist to provide a safe and secure base to build a sense of security and to develop healthy social interactions (Aytac et al, 2019;Backman et al, 2018;McErlean & Lim, 2020). Furthermore, parental warmth and acceptance may protect from internalizing-externalizing problems, however, parental rejection and control may lead to numerous internalizing-externalizing issues (Baumrind, 1966;Rohner, 1986).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Children do not only inherent physical features but also acquire and learn identity, values, interpersonal skills, self-esteem, and self-concept (Rohner, 2004;Shim & Lim, 2019). Affectionate, warmth, positive, caring, and supportive relationship with parents aids the children to develop aninternal model (Bowlby, 1982) which assist to provide a safe and secure base to build a sense of security and to develop healthy social interactions (Aytac et al, 2019;Backman et al, 2018;McErlean & Lim, 2020). Furthermore, parental warmth and acceptance may protect from internalizing-externalizing problems, however, parental rejection and control may lead to numerous internalizing-externalizing issues (Baumrind, 1966;Rohner, 1986).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, low parental emotional responsiveness, and communication, controlling, punitive, rejecting, and harsh parenting is associated with adverse consequences including depression, anxiety, stress, aggression, social isolation, loneliness, substance use, and selfinjurious behaviors (Haslam, Poniman, Filus, Sumargi, & Boediman, 2020;King, Boyd, & Pragg, 2017;Yurasek et al, 2019). Researchers explored that parenting styles have a significant impact on adolescents' adjustment and subsequent development of internalizingexternalizing problems (Aytac, Pike, & Bond, 2019;McErlean & Lim, 2020;McKinney & Kwan, 2018;Shim & Lim, 2019;Zubizarreta, Calvete, & Hankin, 2019). Bowlby (1973) also emphasized the parentchild emotional bonding and its influence on the psychosocial functioning, interpersonal relationships, and well-being of children and adolescents (Haslam et al, 2020;McErlean & Lim, 2020).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, it is worth noting that various studies [79][80][81][82][83] investigated the association between attachment to parents and youth aggression at large, while fewer have specifically investigated the differential influence of attachment to maternal vs. fa-thers on adolescents' aggression. These studies suggested that insecure attachment to fathers, and paternal practices in general, greatly predict increased aggression during adolescence [4,84,85]. Yet, the protective role of secure attachment to mothers was also reported regarding adolescents' aggressiveness [63,86], which was also supportive of adolescents' prosocial behaviors [86].…”
Section: Parental Attachment and Its Association With Alexithymia And...mentioning
confidence: 99%
“…(2015) menemukan individu dengan alexithymia memiliki tingkat agresi yang lebih tinggi dibandingkan individu non-alexithymia. Penelitian Janik McErlean & Lim (2019) dan Li, dkk (2020) juga menemukan bahwa terdapat hubungan positif antara alexithymia dan agresi. Sebaliknya, de Schutter, dkk.…”
Section: P E N D a H U L U A Nunclassified